2022
DOI: 10.1002/exp.20210053
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation‐induced emission luminogens for augmented photosynthesis

Abstract: Photosynthesis is promising in sequestrating carbon dioxide and providing food and biofuel. Recent findings have shown that luminescent materials could shift the wavelength of light to a more usable range for augmented photosynthesis. Among them, aggregation-induced emission luminogens (AIEgens) have advantages of efficient light conversion, high biocompatibility, large Stokes' shift, and so on. In this perspective, emerging reports of augmented photosynthesis with luminescent materials, especially the AIEgens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Photosynthesis in nature transforms the carbon dioxide and water in the atmosphere into carbohydrates with the help of solar energy, providing a rich source of oxygen and energy for all life on earth . The photosynthesis process involves the participation and transformation of multiple substances.…”
Section: Aiegen-based Sunlight Transformationmentioning
confidence: 99%
“…Photosynthesis in nature transforms the carbon dioxide and water in the atmosphere into carbohydrates with the help of solar energy, providing a rich source of oxygen and energy for all life on earth . The photosynthesis process involves the participation and transformation of multiple substances.…”
Section: Aiegen-based Sunlight Transformationmentioning
confidence: 99%
“…Cumulative evidence demonstrated that some aromatic photosensitizers [e.g., chlorophyll (Chl) and curcumin] are natural antibacterial compounds extracted from plants with low toxicity. They have been proved to possess broad bactericidal activity against not only Gram-positive but also Gram-negative bacteria via interacting with cellular components of bacteria. , Chl is a natural photosensitizer for PDT with the advantages of excellent ROS yield and good biocompatibility . To overcome the dilemmas include antibacterial adhesion and bactericidal strategies, both have limitations and most porphyrin-based photosensitizers have toxicity, thus a synergistic antibacterial surface consisting of both superhydrophobic and PDT characteristics would be an interesting strategy to inactivate bacteria without triggering drug resistance and effectively inhibit bacterial infection.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Chl is a natural photosensitizer for PDT with the advantages of excellent ROS yield and good biocompatibility. 30 To overcome the dilemmas include antibacterial adhesion and bactericidal strategies, both have limitations and most porphyrin-based photosensitizers have toxicity, thus a synergistic antibacterial surface consisting of both superhydrophobic and PDT characteristics would be an interesting strategy to inactivate bacteria without triggering drug resistance and effectively inhibit bacterial infection. Herein, we present a superhydrophobic and photodynamic synergistic antibacterial PLA surface achieved via completely non-toxic materials and a facile non-solvent-assisted induced phase separation process (NIPS).…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the fixation of biosamples was required, which would inevitably damage the samples. Compared to these methods, fluorescence imaging technology has been widely employed due to its advantages of simple operation, low damage to living cells, suitable resolution, and real-time observation. Fluorescent probes that enable the simultaneous visualization of two organelles are promising tools to investigate the organelle interactions. Up to now, several cases of dual-target probes have been reported. , For instance, Zheng and colleagues have prepared a fluorescent probe to visualize lysosomes and LDs in different fluorescent colors, which relies on environment-sensitive fluorescent dyes .…”
Section: Introductionmentioning
confidence: 99%